Komitmen Normatif Memediasi Akibat Kemampuan Kerja Serta Ciri Aktiviitas kerja terhadap Prestasi Kerja - Daru Setyo Wahyono; Pahlawansjah Harahap; Indarto Indarto (J-MAS (Jurnal Manajemen dan Sains), 2023)
It was conducted to analyze the impact of work skills and job characteristics on the work performance of Bidlabfor Polda Jateng employees with normative commitment as an intermediary variable. The survey method is a quantitative method using data sources. The population of this survey was 53 personnel of the Central Java Regional Police Forensic Laboratory Division, and the sample was taken using the census technique, namely taking the entire population as respondents to be studied. Data analysis was carried out using descriptive and multiple regression through the SPSS program. Based on data analysis regarding the impact of work skills and work characteristics on work performance of Bidlabfor Polda Jateng employees with normative commitment as an intermediary variable, it can be concluded that normative commitment has the most significant influence in shaping optimal employee work performance. Therefore, the higher the work skills and work characteristics, the better the level of employee performance will be in the presence of strong normative commitment.